PEMANFAATAN APPSHEET UNTUK PENGEMBANGAN APLIKASI PENCATATAN HASIL SURVEY (STUDI KASUS: DISKOMINFO KUKAR) - Ramadhani, Ananda (Universitas Multi Data Palembang, 2025)
Price index is a benchmark for measuring changes in the prices of goods or services circulating within an economic system. In Indonesia, the price index is determined based on data collected by the Central Bureau of Statistics (BPS). In the Statistics Division of the Department of Communication and Information of Kutai Kartanegara Regency (Kukar), several individuals are appointed as enumerators to record the prices from surveys. Previously, the data was manually recorded, which was inefficient and prone to errors compared to automated or digital recording methods. Moreover, inaccurate recording and reporting can impact government and public policies. Therefore, AppSheet is an ideal tool for developing a recording application with a quick development process. The steps to using AppSheet include first creating a database using Excel or Google Spreadsheet, then linking the database to AppSheet, and building the desired features. The result shows that developing a survey data recording application through AppSheet has proven to increase the efficiency of data recording based on testing that has been conducted.